The PICTURE study: diagnostic accuracy of multiparametric MRI in men requiring a repeat prostate biopsy - Simmons,LAM; Kanthabalan,A; Arya,M; Briggs,T; Barratt,D; Charman,SC; Freeman,A; Gelister,J; Hawkes,D; Hu,Y; Jameson,C; McCartan,N; et al. (British Journal of Cancer, 2017)
background: Transrectal prostate biopsy has limited diagnostic accuracy. Prostate Imaging Compared to Transperineal Ultrasound-guided biopsy for significant prostate cancer Risk Evaluation (PICTURE) was a paired-cohort confirmatory study designed to assess diagnostic accuracy of multiparametric magnetic resonance imaging (mpMRI) in men requiring a repeat biopsy.methods: All underwent 3 T mpMRI and transperineal template prostate mapping biopsies (TTPM biopsies). Multiparametric MRI was reported using Likert scores and radiologists were blinded to initial biopsies. Men were blinded to mpMRI results. Clinically significant prostate cancer was defined as Gleason greater than or equal to4+3 and/or cancer core length greater than or equal to6 mm.results: Two hundred and forty-nine had both tests with mean (s.d.) age was 62 (7) years, median (IQR) PSA 6.8 ng ml (4.98–9.50), median (IQR) number of previous biopsies 1 (1–2) and mean (s.d.) gland size 37 ml (15.5). On TTPM biopsies, 103 (41%) had clinically significant prostate cancer. Two hundred and fourteen (86%) had a positive prostate mpMRI using Likert score greater than or equal to3; sensitivity was 97.1% (95% confidence interval (CI): 92–99), specificity 21.9% (15.5–29.5), negative predictive value (NPV) 91.4% (76.9–98.1) and positive predictive value (PPV) 46.7% (35.2–47.8). One hundred and twenty-nine (51.8%) had a positive mpMRI using Likert score greater than or equal to4; sensitivity was 80.6% (71.6–87.7), specificity 68.5% (60.3–75.9), NPV 83.3% (75.4–89.5) and PPV 64.3% (55.4–72.6).conclusions: In men advised to have a repeat prostate biopsy, prostate mpMRI could be used to safely avoid a repeat biopsy with high sensitivity for clinically significant cancers. However, such a strategy can miss some significant cancers and overdiagnose insignificant cancers depending on the mpMRI score threshold used to define whic